2017
DOI: 10.1002/ana.25109
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic core thresholds change with time to reperfusion: A case control study

Abstract: Introduction: We aimed to identify whether acute ischemic stroke patients with known complete reperfusion after thrombectomy had the same baseline computed tomography perfusion (CTP) ischemic core threshold to predict infarction as thrombolysis patients with complete reperfusion. Methods: Patients who underwent thrombectomy were matched by age, clinical severity, occlusion location, and baseline perfusion lesion volume to patients who were treated with intravenous alteplase alone from the International Stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
108
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 23 publications
4
108
1
Order By: Relevance
“…CBF) associated with infarction should progressively increase over time as infarcts grow into penumbra. 2,4 Unlike previous work that showed a relationship between optimal perfusion thresholds and imaging-to-reperfusion time, this analysis, more intuitively, shows that these thresholds are also dependent on onset-toreperfusion-time. 2 Interestingly, the association between optimal CTP thresholds and onset-to-reperfusion time was weaker when patients presented late.…”
Section: Discussioncontrasting
confidence: 61%
“…CBF) associated with infarction should progressively increase over time as infarcts grow into penumbra. 2,4 Unlike previous work that showed a relationship between optimal perfusion thresholds and imaging-to-reperfusion time, this analysis, more intuitively, shows that these thresholds are also dependent on onset-toreperfusion-time. 2 Interestingly, the association between optimal CTP thresholds and onset-to-reperfusion time was weaker when patients presented late.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, only 56.7% of that study population were identified with ICA/M1 occlusion/stenosis, and rFTD is a crude estimation only for occlusion in ICA or proximal M1 large vessel occlusion. We used the ratio between the volume of hypoperfused "penumbral range" tissue (DT >3 seconds) and the volume of tissue within the total DT >3 seconds lesion with more severe delay (DT >6 seconds) to evaluate the collateral flow . DT is essentially a quantification of collateral flow, measuring the time it takes for contrast to arrive in ischemic tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) perfusion (CTP) imaging has been widely used to determine infarct core and penumbra in acute ischemic stroke patients. Cerebral collateral flow can be quantified using CTP imaging data by measuring the volume of tissue with delayed contrast transit instead of conventional CT angiography (CTA) collateral grading . More severe delay in contrast transit indicates poorer collateral flow.…”
mentioning
confidence: 99%
“…Unsurprisingly, ASPECTS scores were lower in patients who presented at a later time from LKN, although there was no significant relationship between time‐to‐imaging and change in perfusion imaging parameters. These data emphasize the role of the noncontrast CT in identifying early and potentially irreversible cerebral infarction when perfusion imaging may show minimal or no areas of “ischemic core.” It is possible that subcritical oligemia (rCBF >30%, for example) may still result in neuronal death—especially in the extended time window—but this degree of hypoperfusion could be missed using thresholds prespecified by RAPID and other automated software platforms. Therefore, it remains critical that perfusion imaging be interpreted in conjunction with the simultaneously acquired noncontrast CT, in accordance with the clinical trials, which demonstrated efficacy using these tools.…”
Section: Discussionmentioning
confidence: 99%